The green lacewing genus Austrochrysa Esben-Petersen, 1928 (Neuroptera: Chrysopidae) from China, with description of two new species - Ma, Yunlong; Yang, Xingke; Liu, Xingyue (Zootaxa, 2020)
A taxonomic study of the green lacewing genus Austrochrysa Esben-Petersen, 1928 from China is presented. Three species of Austrochrysa are recorded from China. Two new species, Austrochrysa lihongyui sp. nov. and Austrochrysa angusta sp. nov., which are described in this study, and a new combination, i.e. Austrochrysa tropica (Yang & Wang, 1994) comb. nov., is proposed. The genus Yunchrysopa Yang & Wang, 1994 is here considered as a junior synonym of Austrochrysa Esben-Petersen, 1928.